Merchant Guilds (Consulados de Comercio) in the Spanish World - Woodward, Ralph Lee (History compass, 2007)
Recent emphasis on the social and cultural history of colonial Latin America has lessened the former growth of economic and institutional history in the region. Yet there is still need for further research on economic elites and their institutions. Merchant guilds were an important element in the economic and judicial development of the Spanish world from the thirteenth to the nineteenth century. Beginning in Catalonia, they later appeared in Castile, and later yet in Spain's overseas dominions, providing import-export merchants with a tribunal for commercial litigation and an institution for the protection and promotion of their commerce. Revitalization of the institution in the eighteenth century extended commercial monopolies to more merchant communities, but also established stronger state control over them. The institution declined and largely disappeared during the nineteenth century. Principal studies of the various consulados in Spain and the Indies are referenced in the endnotes.